A Second Look at the Roles of Quit Rates and Exceptional Variables in the Determination of Money Wages - J.C.R. Rowley; D.A. Wilton (Queen's University, Department of Economics, 1972)
In his recent discussion of wage-determination in the U.S. manufacturing industry and its durable and non-durable components, Arthur Donner attempts to explore the short-run interaction of labour turnover and inflationary expectations by incorporating this interaction into a "a two-equation model suitable for econometric testing". His tentative conclusions concern both the direct roles of these variables and the speeds of adjustment of wage changes to prior expectational changes. Since theoretical analyses cannot establish the quantitative significance of biases and false inferences, our numerical results provide important results with respect to the robustness of Donner's estimates. They appear to confirm a significant role for excess demand, but the effect of inflationary price expectations remains uncertain in the absence of prior information with respect to the speeds of adjustment to such expectations. In his list of tentative conclusions, Donner cites one particular result which he had not anticipated. "The implication that the wholesale price index fits into the estimating equation slightly better than the consumer prices is somewhat startling at first, but may present some support for the hypothesis that prices and wages are raised when labour supply tightens–and particularly when vacancies rise above their steady-state values. There appears to be some tentative support in these findings for the hypothesis that the money illusion exists in the short-run." Our results suggest that the use of the wholesale price index (WPI) leads to substantially better fits than the use of the consumer price index (CPI) for both total manufacturing and its separate components. Finally, a model which contains the unusual specification of wage expectations as an explanatory variable for money wage changes is conclusively rejected by our results.
Keywords: 330